Colloidal stability and cadmium removal efficiency of chitosan-modified magnetite nanoparticles from mill scale waste - Ahmad Nazri, Nur Asyikin; Azis, Raba'ah Syahidah; Ismail, Ismayadi; Che Man, Hasfalina; Kasmuri, Norhafezah; Nakajima, Hideki; Chanlek, Narong; Megat Hanafiah, Megat Ahmad Kamal (Elsevier B.V., 2026)
Industrial millscale waste offers a low-cost and sustainable source of magnetite for nanomaterial synthesis, but its application in water remediation remains underexplored. This study aims to develop and evaluate a surfactant-free magnetic chitosan nanocomposite (MagChi NC), synthesized from millscale-derived magnetite, for enhanced colloidal stability and cadmium (Cd(II)) removal. Optimal heterocoagulation was achieved at pH 3 for chitosan and pH 7 for magnetite. Structural and surface characterizations (XRD, FTIR, HRTEM, FESEM, XPS, zeta potential, and BET analyses) confirmed successful chitosan coating and improved dispersion stability. Adsorption studies revealed that MagChi NCs exhibited a markedly higher Cd(II) uptake (30.6 mg/g) compared to unmodified magnetite nanoparticles (10.9 mg/g), with rapid equilibrium attained in 15 min at pH 6 and 3 g/L dosage. Kinetic and isotherm modeling indicated pseudo-second-order kinetics and Langmuir-type monolayer adsorption. Mechanistic insights from FTIR and XPS suggested that Cd(II) removal proceeds via electrostatic attraction, cation exchange, and coordination interactions. The findings highlight a sustainable and scalable approach to transform industrial waste into high-performance nanosorbents, offering a promising pathway for heavy metal remediation in water treatment.